Essential headaches in developmental age: What is changed before, during and after the lockdown for COVID-19 pandemic. Clinical study - Bonuccelli, Alice; Depietri, Greta; Baldaccini, Tommaso; Ricciutelli, Irene; Peroni, Diego; Spalice, Alberto; Massimetti, Gabriele; Morganti, Riccardo; Orsini, Alessandro; Striano, Pasquale (Frontiers in Pediatrics, 2023)
INTRODUCTION: Essential headache is one of the main causes of pain in children, with an important impact on their quality of life. In children with essential headaches play an important role in both triggers (stress, video terminals, physical fatigue) but also comorbidities (anxiety, depression, and sleep disturbances). CoViD-19 Pandemic was stressful, especially for children, and amplified all headache triggers and comorbidities. STUDY OBJECTIVE: We studied the aspects concerning the headache, lifestyle, habits, and mental health of children before, during, and after the lockdown and the differences between some categories (selected by age, gender, and headache status before the lockdown). METHODS: This study was conducted on 90 patients with primary headaches followed at the AOUP Neuropediatrics Clinic from January 2018 to March 2022. Participants answered a questionnaire of 21 questions. For every question, the answer was divided into three periods: before, during, or after the lockdown. All dates have been converted and inserted into a database and we used SPSS technology for statistical analysis. RESULTS: 51,1% were females, 48,9% were males and there was a prevalence of adolescents (56,7%) compared to children from 5 to 11 years (43,3%). Regarding the headache onset, 77,7% of patients started to suffer from headaches before 10 years, moreover, 68,9% had familiarity with the headache. Using Cohen’s K- Concordance Test, we performed a Concordance Analysis, studying the questions in the three periods above mentioned: considering headache characteristics there is poor concordance about the trend of headache; modest concordance about the frequency and the type (migraine or tension headache); moderate concordance about the acute use of analgesic. Analyzing lifestyle the lockdown had a significant impact on sports (practiced much less) and on the use of video terminals (used much more). CONCLUSION: The pandemic and lockdown aren't events that led to strong and unidirectional responses in patients, there is variability in the answers about headache, lifestyle, and psychology, and each patient had individualized reactions. However, these considerations are not applied to physical activity and the use of video terminals, because both have been inevitably modified by the pandemic situations and so were not affected by subjective influence.